Validating the name Begonia urunensis (Begoniaceae) - Zhao, Cheng-Hao; He, Hai (Phytotaxa, 2016)
The name Begonia urunensis Kiew (2001: 283; Begoniaceae) was first proposed based on material collected from the Malaysian state Sabah in Borneo. Notably, Kiew (2001) cited a single gathering deposited in two herbaria (R. Kiew & S. Anthonysamy RK 4473 in SAN & SING) as its type, which was against Art. 40.7 of the International Code of Nomenclature for algae, fungi, and plants (ICN; McNeill et al. 2012). Therefore this name was actually not validly published, and that Kollmann & Freitas (2016) considered the two duplicates of RK 4473 in SAN & SING to be syntypes was a mistake since Art. 9.5 of ICN (McNeill et al. 2012) is not applied for a name not validly published. Though Kollmann & Freitas (2016) traced the original material and only found a single specimen of RK 4473 in SING, their treatment did not make the name Begonia urunensis validly published because their designation of the “lectotype” contrary to Art. 40.6 and Art. 40.4, Ex. 4 of ICN (McNeill et al. 2012). Hence we hereafter validate this name accordingly.